2021
DOI: 10.37616/2212-5043.1260
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining occurrence of arrhythmias in patients post-closure of atrial septal defects

Abstract: Objectives This study aimed to determine the risk factors for the occurrence of arrhythmias after either transcatheter or surgical closure of atrial septal defect. Methods This prospective study included 150 patients admitted for transcatheter or surgical closure of atrial septal defect. Transthoracic echocardiography together with a twelve-leads ECG were done during 1 and 3 months follow up. The paired T, chi-square and Logistic regression tests were used to detect any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Постперикардиотомный синдром развивается в первые несколько дней/недель после операции, сопровождаясь лихорадкой, болью в грудной клетке и животе, рвотой, слабостью, одышкой, что отмечается на ЭхоКГ появлением жидкости в полости перикарда и плевральной полости с риском развития тампонады сердца. Интересно отметить, что долгосрочное наблюдение (более 40 лет) среди пациентов, которым была проведена операция с искусственным кровообращением, демонстрирует редкое развитие осложнений (обычно это наджелудочковые аритмии, легочная гипертензия), риск их оказался выше у пациентов, возраст которых на момент операции был старше 25 лет [28].…”
Section: резюме _____________________________________________________...unclassified
“…Постперикардиотомный синдром развивается в первые несколько дней/недель после операции, сопровождаясь лихорадкой, болью в грудной клетке и животе, рвотой, слабостью, одышкой, что отмечается на ЭхоКГ появлением жидкости в полости перикарда и плевральной полости с риском развития тампонады сердца. Интересно отметить, что долгосрочное наблюдение (более 40 лет) среди пациентов, которым была проведена операция с искусственным кровообращением, демонстрирует редкое развитие осложнений (обычно это наджелудочковые аритмии, легочная гипертензия), риск их оказался выше у пациентов, возраст которых на момент операции был старше 25 лет [28].…”
Section: резюме _____________________________________________________...unclassified
“…A study conducted by Clark which included 15 patients with secundum ASD showed that 5 patients presented sinus node dysfunction or atrioventricular node dysfunction before repair [ 14 ]. On the other hand, atrioventricular block post-transcatheter closure of ASD occurs in rare instances, and it can be transient or may progress to complete heart block [ 15 ]. When compared with patients with unclosed ASD, Albaek et al showed that those with interventional ASD closure were at higher risk of developing atrioventricular block, incomplete right bundle branch block, or left anterior fascicular block and had a higher demand for pacemaker implantation [ 16 ].…”
Section: Arrhythmias and Conduction Disorders Associated With Asdmentioning
confidence: 99%
“…Mansour et al demonstrated that age, P wave dispersion, the systolic myocardial velocity of the right ventricle (S’), and systolic pulmonary artery pressure are independent risk factors for atrial arrhythmias in multivariate analysis [ 15 ]. Moreover, Van de Bruaene et al proposed a risk score, in which male gender, atrial arrhythmia before repair, atrial arrhythmia ≤ 1 month, and systolic pulmonary artery pressure ≥ 25 mmHg are predisposing factors in the development of late atrial arrhythmias [ 23 ].…”
Section: Predictors Of Arrhythmias After Asd Interventional Closurementioning
confidence: 99%
See 1 more Smart Citation